EVALUATION BORON AVAILABILITY IN SOME SOILS OF DIYALA PROVICIAL AND ITS CORRELATION WITH SOME SOIL CHARACTERS AND AVAILABLE CALCIUM BORON RATIO IN THE SOIL - Mohammed, Adnan Ali; Abdulrassol, Qahtan J. (Diyala Agricultural Sciences Journal, 2020)
The study carried out at soil samples from 10 different regions of Diyala province, cultivated and uncultivated, to evaluate the available boron in these soils and its relation to some soil properties, EC, pH, O.M, Clay content and percentage of carbonate minerals .As well as the ratio of available Ca/B in the soil was studied and its effect on the availability of boron. The results showed that the concentration of available boron in the cultivated soils ranged between 3.74 - 15.2 mg kg-1 soil and ranged between 3.62 – 18.9 mg kg-1 soil in uncultivated soils .The result also showed a significant negative correlation between available boron and soil pH and positive correlation with electrical conductivity and positive correlation with soil organic matter in cultivated soils . The correlation coefficients with carbonate minerals and clay were not significant in both cultivated and uncultivated soils. It is also no significant correlation with soil organic matter in uncultivated soils. The results also showed that the ratio of available Ca/B in the cultivated soils ranged between 657.2 -1604.3 and between 523.9- 1817.7 in uncultivated soils .According to traditional criteria critical nutrient limits the study soils are rich in available boron and does not need fertilization .According to the Ca/B criteria , 85% of the study soils, needs fertilization because the available Ca/B ratio is higher than 650/1.